Corporeality, Morality and Soul of Man in the Treatises by Innokenty Gizel - Fedko, O. M. (Anthropological Measurements of Philosophical Research, 2025)
Purpose. The study aims to analyse anthropological images of human corporeality and morality in the treatises of the Ukrainian theologian and philosopher of the Baroque era, Innokenty Gizel. His creative synthesis of Orthodox ideas, which represents a humanistic model of understanding man, deserves special attention. Theoretical basis. The methodological basis consists of the basic provisions of historical and philosophical analysis, hermeneutics, and a cultural-anthropological approach. The theoretical basis is provided by works on the history of Ukrainian Baroque thought and Gizel’s philosophical and theological texts. Originality. The author attempts a comprehensive reconstruction of Innokenty Gizel’s anthropological concept in the context of Ukrainian Baroque. Baroque anthropology is considered as a synthetic system that combines the rationalistic, moral-ethical, and spiritual dimensions of human existence. It has been determined that Gizel forms his own model of Christian humanism as a combination of Orthodox spirituality and rationalistic philosophy. The understanding of the soul as a spiritual and rational substance that integrates the physical, moral and cognitive principles is clarified. Conclusions. The anthropological concept of Innokenty Gizel represents a new stage in the development of Ukrainian philosophical and theological thought of the 17th century. At the heart of his teachings is the human being as a spiritual and moral creature, called upon to seek harmony with God through knowledge, repentance and free will. His treatises reflect a dialectical combination of the physical and spiritual, the rational and moral in man, which corresponds to the Baroque idea of the unity of opposites. Gizel created an original Ukrainian version of Christian humanism, in which moral perfection and inner freedom form the basis of true human existence. Thus, the legacy of Innokenty Gizel is an important source for understanding the formation of the Ukrainian anthropological tradition and the development of spiritual culture in the Baroque era.